Macrocyclic bis(ureas) as ligands for anion complexation - Kretschmer, Claudia; Dittmann, Gertrud; Beck, Johannes (Beilstein Journal of Organic Chemistry, 2014)
Two macrocyclic bis(ureas) 1 and 2, both based on diphenylurea, have been synthesized. Compound 1 represents the smaller ring with two ethynylene groups as linkers and 2 the larger ring with two butadiynylene groups. On thermal treatment to 130 °C molecule 1 splits up into two dihydroindoloquinolinone (3) molecules. Both compounds 1 and 2 form adducts with polar molecules such as dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) and act as complexing agents towards a series of anions (Cl−, Br−, I−, NO3−, HSO4−). The crystal structures of 3, 2·2DMSO, 2·2DMF, and of the complex NEt4[Br·2] have been determined. Quantitative investigations of the complexation equilibria were performed via 1H NMR titrations. While 1 is a rather weak complexing agent, the large ring of 2 binds anions with association constants up to log K = 7.93 for chloride ions.
Keywords: anion binding; macrocyclic compounds; NMR spectra; supramolecular chemistry; template; urea

Comprehensive Supramolecular Chemistry - Atwood, J. L.; Davies, J. E. D.; MacNicol, D. D.; Vögtle, F.; Lehn, J.-M. (Pergamon, Elsevier Science Ltd., 1996)

Supramolecular Chemistry - Steed, J. W.; Atwood, J. L. (John Wiley & Sons, 2009)

(untitled) - Beer, P. D.; Gale, P. A. (Angew. Chem., Int. Ed., 2001)

Thematic issue on Supramolecular Chemistry of Anionic Species - Gale, P. A.; Gunnlaugson, T. (Chem. Soc. Rev., 2010)

(untitled) - Gale, P. A. (Chem. Commun., 2011)

(untitled) - Custelcean, R.; Remy, P.; Bonnesen, P. V.; Jiang, D.; Moyer, B. A. (Angew. Chem., Int. Ed., 2008)

(untitled) - Wu, B.; Liang, J.; Yang, J.; Jia, C.; Yang, X.-J.; Zhang, H.; Tang, N.; Janiak, C. (Chem. Commun., 2008)

(untitled) - Zhang, Y.; Zhang, R.; Zhao, Y.; Ji, L.; Jia, C.; Wu, B. (New J. Chem., 2013)

(untitled) - Chang, K.-J.; Moon, D.; Lah, M. S.; Jeong, K.-S. (Angew. Chem., Int. Ed., 2005)

(untitled) - Beck, J.; Hörner, M.; Dittmann, G. (Eur. J. Inorg. Chem., 2009)

(untitled) - Swinburne, A. N.; Paterson, M. J.; Beeby, A.; Steed, J. W. (Chem.–Eur. J., 2010)

(untitled) - Stadlbauer, W.; Kappe, T. (Monatsh. Chem., 1984)

(untitled) - Mulwad, V. V.; Lohar, M. V. (Indian J. Chem., Sect. B, 2003)

(untitled) - Zhang, X.; Zhang-Negrerie, D.; Deng, J.; Du, Y.; Zhao, K. (J. Org. Chem., 2013)

(untitled) - Li, H.; Yang, H.; Petersen, J. L.; Wang, K. K. (J. Org. Chem., 2004)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A, 2008)
The crystal structure solutions and refinements were performed using the Shelx programs (Shelxs93 and Shelxl93): G. M. Sheldrick, Shelx-Programs for Crystal Structure Solution and Refinement. All details concerning the crystal structure determinations may be found in the Supporting Information File 1.

Spartan 10, Program for Calculation of Molecular Properties (Wavefunction Inc.)

(untitled) - Hynes, M. J. (J. Chem. Soc., Dalton Trans., 1993)